Exploring the Determinants of Customer Loyalty in OTC Drugs: Evidence from PT Phapros Tbk, Banten - Basuki Rahmat; Jaja Suteja; Popo Suryana (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study explores the determinants of customer loyalty in the over-the-counter (OTC) pharmaceutical industry by examining the roles of brand image, price perception, and product quality, with customer trust as a mediating variable. The research focuses on customers of PT Phapros Tbk operating in the Banten region, where competition in the OTC market is intense and consumer trust is critical due to the health-related nature of the products. A quantitative approach was employed using survey data collected from pharmacy and drugstore owners, which were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that brand image, price perception, and product quality have significant positive effects on customer trust and customer loyalty. Furthermore, customer trust is found to significantly influence customer loyalty and to mediate the relationships between brand image, price perception, product quality, and customer loyalty. These findings indicate that customer loyalty in the OTC pharmaceutical sector is shaped not only by functional and economic considerations but also by trust-based evaluations developed through consistent and credible firm behavior. This study contributes to the literature by reinforcing trust-based loyalty models in the pharmaceutical context and offers practical implications for pharmaceutical firms seeking to strengthen long-term customer relationships through trust-oriented strategies.